Intersectionalisation as meta-discursive practice: complicated power dynamics in Pink Dot's movement-building. - Lazar, Michelle M. (Critical Discourse Studies, 2024)
This article adopts the combined perspectives of critical discourse studies and (critical) intersectionality studies to examine efforts at movement-building by Pink Dot SG, an LGBTQ group, which has developed within the illiberal geopolitical space of Singapore. The term 'intersectionalisation' is introduced to refer to a reflexive meta-discursive strategy which mobilizes the intersectionality of social identities (such as gender, sexuality, race, class, generation, and nationality) to advance particular sociopolitical objectives. The article illustrates three ways intersectionalisation operates in Pink Dot's official videos: (i) to create solidarities within the LGBTQ community; (ii) to advocate for the LGBTQ community by straight allies, and (iii) to forge alliances dialogically between queer and straight communities in Singapore. The analysis of the videos shows that interactions between various assemblages of intersectional identities of privilege and marginality are brought to the fore in building the social movement, and how its discourse navigates a terrain of complicated power dynamics.